Effects of the attributes of school management teams on the management of quality education: towards school effectiveness - Israel, Kariyana (Penerbit Universiti Kebangsaan Malaysia, 2023)
Ascertain attributes of school management team (SMT) members as determinants of education quality. Participants were 60 SMT members randomly sampled from the 20 participating schools. Questionnaire reliability and validation were respectively determined by Cronbach’s alpha coefficient and through a pilot study. Quantitative data were descriptive statistically analysed using SPSS version 22 and qualitative data through content analysis. The study found that SMTs were aware that there were legislation mandates that guide the management of quality education but viewed schools as not utilising such mandates. SMTs also viewed schools as having clear vision and mission statements which they neither displayed nor implement. Most factors that support high-quality education were missing in schools. Participants believed that holding SMTs responsible for subpar school performance and performance measurement and monitoring were necessary prerequisites for the provision and administration of high-quality education. Recommendations included mandating SMTs to effectively manage each school's physical and human resources in accordance with legislative requirements.